Evaluating the PROMIS-29 v2.0 for Use Among Older Adults with Multiple Chronic Conditions - Rose, Adam J. (Qual Life Res, 2018)
PURPOSE: The Patient-Reported Outcomes Measurement Information System 29-item profile (PROMIS-29 v2.0), which measures health-related quality of life (HRQoL), has had limited evaluation among older adults (age 65+) with multiple chronic conditions. Our purpose was to establish convergent validity for PROMIS-29 in this population. METHODS: We collected the PROMIS-29 v2.0 and the Veterans RAND 36 (VR-36) for 1,359 primary care patients age 65+ with at least 2 of 13 chronic conditions, oversampling those age 80+. We conducted multiple analyses to examine score differences across subgroups, differential item functioning (DIF), and comparisons of PROMIS-29 v2.0 and VR-36 scores. RESULTS: The mean age was 80.7, and all patients had at least 2 of 13 chronic conditions. Older age, female sex, Hispanic ethnicity, and more chronic conditions were associated with worse physical health scores (PHS) and mental health scores (MHS) on the PROMIS-29 v2.0 – findings which are in the expected direction. None of the 700 pairs of items met criteria for DIF. PHS and MHS were highly intercorrelated (r = 0.74, p < 0.001 for this and all other findings). PHS was more highly correlated with the VR-36 Physical Component Score (PCS) than the Mental Component Score (MCS) (r = 0.85 and 0.32, respectively), while MHS was highly correlated with both (r = 0.70 and 0.64, respectively). CONCLUSIONS: PROMIS-29 v2.0 demonstrates expected bivariate relationships with key person-level characteristics and does not show DIF. PROMIS-29 v2.0 scores are highly correlated with VR-36 scores. These results provide support for the validity of PROMIS-29 v2.0 as a measure of HRQoL among older adults with multiple chronic conditions.